Effects of Baby Schema and Mere Exposure on Explicit and Implicit Face Processing - Venturoso, Leonardo; Gabrieli, Giulio; Truzzi, Anna; Azhari, Atiqah; Setoh, Peipei; Bornstein, Marc H.; Esposito, Gianluca (Frontiers in Psychology, 2019)
In an increasingly multicultural society, the way people perceive individuals from the same vs different ethnic groups greatly affects their own and societal well-being. Two psychological effects that influence these perceptions are the Mere-Exposure Effect (MRE), wherein familiarity with certain objects or persons suffices for people to develop a preference for them and the Baby Schema (BS), a set of specific facial features that evoke caregiving behaviors and an affective orientation in adults. In the present study, we aimed to investigate whether these two effects play a role in physiological responses to babies’ vs adults’ faces belonging to participants’ in-group vs out-group. In study 1, the pupillary diameter of 62 Caucasian participants (M=31; F=31) who observed adult and infant faces of different ethnic groups (Caucasian, Chinese) was measured. In study 2, brain waves of 38 Caucasian participants (M=19; F=19), who observed the same set of faces, were recorded using EEG. In both studies, adults’ explicit preferences (i.e., attitudes) towards faces were assessed using questionnaires. In Study 1, females showed greater attention to infant than adult faces (BS-effect) in both pupils, regardless of the ethnic group of the face. By contrast, males attended to infant more than adult faces for out-group faces only (BS effect). In Study 2, greater left posterior-parietal alpha activation towards out-group compared to in-group adult faces was found in males (MRE). Participants with a low BS effect towards in-group baby faces exhibited greater left posterior alpha activation to out-group than in-group baby faces (MRE). These findings reveal how different levels of sensitivity to in-group infants may moderate perceptions of both in-group and out-group babyfaces. Questionnaire measures on attitudes showed that males and females preferred in-group to out-group adult faces (MRE). Participants in Study 2 also reported a greater preference for infants’ than adults’ faces (BS effect). These findings explicate the roles of gender and the Baby Schema effect in moderating implicit processing of in-group and out-group faces, despite their lack in moderating explicit reports. Contradictory findings at the implicit (physiological) and explicit (self-report) levels suggest that differential processing of faces may occur at a non-conscious level.